2022
DOI: 10.3390/ijms24010280
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus MJM60383 Inhibits Lipid Accumulation in Caenorhabditis elegans Induced by Enterobacter cloacae and Glucose

Abstract: Gut microbiota are known to play an important role in obesity. Enterobacter cloacae, a Gram-negative bacterium, has been considered a pathogenic bacterium related to obesity in the gut. In this study, we established an obesity model of C. elegans by feeding E. cloacae combined with a high glucose diet (HGD), which significantly induced lipid accumulation. An anti-lipid mechanism study revealed that the fatty acid composition and the expression level of fat metabolism-related genes were altered by feeding E. cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…An interesting study performed by Gu et al [36] described the efficacy of a probiotic strain of Lactobacillus pentosus MJM60383 in an obese model of C. elegans (Table 1). In this work, they established a new obesity model by feeding this nematode with a culture of Enterobacter cloacae, a proposed pathogenic bacterium that induces obesity in germ-free mice, in combination with high-glucose (100 mM) conditions (HGD-E) [36]. The proposed C. elegans obese model was characterized by an increase in the lipogenic and a decrease in the β-oxidation genes.…”
Section: Other Lactic Acid Bacteria With Anti-obesity Properties In C...mentioning
confidence: 99%
See 4 more Smart Citations
“…An interesting study performed by Gu et al [36] described the efficacy of a probiotic strain of Lactobacillus pentosus MJM60383 in an obese model of C. elegans (Table 1). In this work, they established a new obesity model by feeding this nematode with a culture of Enterobacter cloacae, a proposed pathogenic bacterium that induces obesity in germ-free mice, in combination with high-glucose (100 mM) conditions (HGD-E) [36]. The proposed C. elegans obese model was characterized by an increase in the lipogenic and a decrease in the β-oxidation genes.…”
Section: Other Lactic Acid Bacteria With Anti-obesity Properties In C...mentioning
confidence: 99%
“…The proposed C. elegans obese model was characterized by an increase in the lipogenic and a decrease in the β-oxidation genes. With this model, they demonstrated that supplementation with L. pentosus MJM60383 strain was able to significantly reduce C. elegans fat accumulation, counteracting the effect of the obesity-related pathogenic bacteria E. cloacae [36].…”
Section: Other Lactic Acid Bacteria With Anti-obesity Properties In C...mentioning
confidence: 99%
See 3 more Smart Citations